SNP Alleles Associated With Low Bolting Tendency in Sugar Beet - Ravi, Samathmika; Campagna, Giovanni; Della Lucia, Maria Cristina; Broccanello, Chiara; Bertoldo, Giovanni; Chiodi, Claudia; Maretto, Laura; Moro, Matteo; Eslami, Azam Sadat; Srinivasan, Subhashini; Squartini, Andrea; Concheri, Giuseppe; et al. (Frontiers in Plant Science, 2021)
The identification of efficient molecular markers related to low bolting tendency is a priority in sugar beet (Beta vulgaris L.) breeding. This study aimed to identify SNP markers associated with low bolting tendency by establishing a genome-wide association study. An elaborate 3-years field trial comprising 13 sugar beet lines identified L14 as the one exhibiting the lowest bolting tendency along with increased survival rate after autumnal sowing. For SNP discovery following the phenotyping, 24 non-bolting and 15 bolting plants of the L14 line were sequenced using Restriction site-associated DNA sequencing (RAD-seq). A GWAS model was established with a set of 10,924 RAD-based SNP markers. The allelic status of the most significantly associated SNPs (p<0.01) was confirmed on three different validation datasets comprising diverse sugar beet lines and varieties adopting a range of SNP detection technologies. This work has led to the identification of SNP_36780842 and SNP_48607347 linked to low bolting tendency and can be used for marker-assisted breeding and selection in sugar beet.